Proceedings of the Twenty-Sixth International Joint Conference on Artificial Intelligence 2017
DOI: 10.24963/ijcai.2017/653
|View full text |Cite
|
Sign up to set email alerts
|

When Will Negotiation Agents Be Able to Represent Us? The Challenges and Opportunities for Autonomous Negotiators

Abstract: Computers that negotiate on our behalf hold great promise for the future and will even become indispensable in emerging application domains such as the smart grid and the Internet of Things. Much research has thus been expended to create agents that are able to negotiate in an abundance of circumstances. However, up until now, truly autonomous negotiators have rarely been deployed in real-world applications. This paper sizes up current negotiating agents and explores a number of technological, societal and eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 29 publications
(4 reference statements)
0
27
0
1
Order By: Relevance
“…The results presented in this article come from the online version of the Lemon Car Game. In the future we would like to use the computer-mediated game in the person-to-person modality-i.e., have two human players play via a screen, rather than face-to-face (e.g., Colored Trails (Ficici et al 2008))-as well as to explore how computer software agents can assist the negotiators (Baarslag et al 2017). The growth in electronic negotiations in international business incentives this research (Melzer and Schoop 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The results presented in this article come from the online version of the Lemon Car Game. In the future we would like to use the computer-mediated game in the person-to-person modality-i.e., have two human players play via a screen, rather than face-to-face (e.g., Colored Trails (Ficici et al 2008))-as well as to explore how computer software agents can assist the negotiators (Baarslag et al 2017). The growth in electronic negotiations in international business incentives this research (Melzer and Schoop 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Automated negotiation research revealed several benefits that computerized negotiation can offer to e-markets. These benefits include: (1) better deal (win-win settlement); (2) decreased transaction cost and time associated with human operation; (3) increased efficiency of settlements even for semi-structured, multi-issue business bargaining problems; and (4) minimizing of some negative aspects of human negotiation, such as avoiding face-to-face encounters with people who are uncomfortable with "bargaining" [5,16,17]. Unfortunately, a poorly designed automated negotiation agent will not be able to deal effectively with a skillful human counterpart that can adopt flexible strategies [5,17].…”
Section: Study Backgroundmentioning
confidence: 99%
“…The topic of automated negotiation has received wide attention in the literature due to its importance as one way of communication between agents and also between agents and humans [3,17,18]. In a general automated negotiation, an agent may need to negotiate with other agents or humans whose (personality) type may not be known [2,24].…”
Section: Introductionmentioning
confidence: 99%